Kerangka Kemitraan antara Badan Usaha Milik Kampung dan Koperasi Desa/ Kelurahan Merah Putih dalam Mendukung Program Kampung Hijau Menuju Ekonomi Desa Hijau di Kabupaten Siak - Sofyan Hadi; Raja Muhammad Amin; Rury Febrina; Auradian Marta; Margina Ferlan; Meris Essio Mento (Nakhoda: Jurnal Ilmu Pemerintahan, 2026)
The Green Village program is the primary instrument for implementing Siak Regency Regional Regulation No. 4 of 2022, which emphasizes village development based on a green economy and environmental sustainability. Siak Regency has two dominant types of village-level economic institution: village-owned enterprises (BUMDes, the national designation; or BUMKam, used in regions including Siak Regency) and Red-and-White rural/urban village cooperatives (KDKMPs), the latter launched underPresidential Instruction No. 9 of 2025. Both are mandated to strengthen the village economy, yet no structured partnership model currently exists. Previous studies tend to discuss BUMDes/BUMKam and KDKMPs separately, with limited attention to their institutional relationship in the context of green village governance. This study formulates a partnership framework aligned with the Green Village program, employing a qualitative exploratory design through in-depth interviews, focus group discussions, observation, and document analysis. Data were analyzed thematically using the Global Gotong Royong Tetrapreneur framework-Chainpreneur, Marketpreneur, Qualitypreneur, and Brandpreneur. The findings indicate that the BUMKam–KDKMP partnership is relevant to supporting green village economy development in Siak Regency, although implementation faces challenges including differences in institutional readiness and potential functional overlap. This study proposes a Tetrapreneur-based partnership model intended to clarify the division of roles and reduce functional overlap, offering a potential practical approach to strengthening institutional synergies and supporting the transition to a green village economy.